Mechanism Analysis of a Low-Frequency Disc Brake Squeal Based on an Energy Feed-In Method for a Dual Coupling Subsystem - Yidong Wu (Shock and Vibration)
Brake squeal is a major component of vehicle noise. To explore the mechanism of the low-frequency brake squeal, a finite element model of an automobile disc brake was established, and a complex mode numerical simulation was performed. According to the unstable modes stemming from the complex modal analysis results, the low-frequency range brake squeal can be determined. Based on an energy feed-in method, the coupling subsystems of the piston-caliper and the disc-pad were established, and a calculation formula for the feed-in energy of the dual coupling subsystem was derived. The results showed that when the feed-in energy of the dual coupling subsystem is close to zero, the complex mode cannot be excited at the corresponding frequency. In addition, the difference in feed-in energy between the two coupling subsystems is positively correlated with the probability of the brake squeal, which can be used to determine the complex mode under which the brake squeal may occur. The greater the feed-in energy of a coupling subsystem is, the more likely it is that the maximum brake vibration mode will appear at this subsystem or its adjacent parts. The increase in brake oil pressure will eliminate some lower-frequency sounds but will not change the frequency of the original low-frequency brake squeals.